PENGARUH MODIFIKASI KABAM (TRAP) TERHADAP HASIL TANGKAPAN IKAN SELUANG (Rasbora sp) - Siti Aminah (Fish Scientiae, 2019)
This research aims (1) to find out the difference of the amount of the catch (catch) obtained from the modification of plastics with bamboo Kabam. 2) to find out the effectiveness of both kabam better for use in catching fish seluang (Rasbora sp.). The methods used are Random Design Group with 2 treatments, namely treatments A: 10 units Kabam plastic and treatment B: 10 units Kabam bamboo. Of research results obtained in (1) the modification of the Kabam (Trap) that can distinguish the amount of the catch (catch) are obtained, (2) capture tool kabam bamboo can generate the average number offish and bigger fish weight compared with capture tool kabam plastic, so that it is more effective for the bamboos kabam catch fish seluang (Rasbora sp).